The Existence of Islamic Financial Institutions in Improving Community Economic Levels (Case Study of PT. BPRS Alwasliyah Krakatau Medan) - Husni Mubarak; Siti Kadariah (Institute of Computer Science (IOCS), 2020)
The existence of financial institutions, especially the banking sector, occupies a very strategic position in bridging the needs for working capital and investment in the real sector with the owners of funds. Availability of sources of funds for the business world and supported by ease of investment encourages business expansion, especially by large-scale groups. The formulation of the problem in this research is, how is the existence of Islamic financial institutions in improving the economic level of the community, what are the factors that are carried out by PT. BPRS Alwasliyah Kraktau Medan in increasing the economic level of the community, how is the LKS exsintesi solution in the welfare of society. The purpose of this research is to know the existence of Islamic financial institutions in improving the economic level of the community, to determine the factors of PT. BPRS Alwasliyah Kraktau Medan in improving the economic level of the community, to find out LKS exsintesi solutions in the welfare of the community. The research method is qualitative research, data is generated from interviews and is supported by documentation and literature study. The results of the study show that in 2017 the contribution of MSMEs to GDP reached Rp. 7,704,635.90 billion with a growth of 60 percent of the total existing businesses, namely, micro businesses contributed 36.82 percent, medium businesses 13.57 percent, and small businesses amounting to 9., 61 percent, the number of customers of PT BPRS Alwasliyah Krakatu Medan in 2018 was 240 larger than in 2017, namely 232 customers, this proves that murabahah financing has an active role in influencing the MSME business sector.